The Effectiveness of The Islamic Communication Strategy for The Personnel of The Indonesian State Police In Overcoming Drug Abuse In The View Of Islamic Education - Herwansyahputra Herwansyahputra; Syukur Kholil; Ahmad Tamrin Sikumbang (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The phenomenon of drug abuse among the general public is becoming increasingly concerning, owing to the ever-increasing activity of drug trafficking, which has spread not only among adults but even among youngsters. The use of drugs has the potential to damage the young generation's potential as the nation's successor. The high circulation of drugs in Belawan Port is due to Belawan's proximity to the sea, which allows for the simple entry and exit of items such as drugs. This is clearly without reason, as several incidents of drug trafficking by water have been discovered.This research falls under the category of field research with a qualitative methodology. The data collected through this research is data related to the problem or research focus, namely Islamic communication strategies in overcoming drug abuse in the Port Police. The analysis process is carried out by domain analysis.Police-community Islamic connection must be maintained. Because communication is the foundation of all police-community relationships. As a result, police officers must mirror community values. Good communication will bring their interests and desires together. Communication strengthens social relationships. Communication assists the police and the community in understanding needs and desires. It is possible to communicate both verbally and nonverbally.In carrying out its communication plan to minimize or reduce drug consumption, which continues to spread until youngsters, numerous communication techniques are used, including: a. The redundancy method, which involves influencing the younger generation of Muslims by repeating messages. b. The canalizing strategy, which entails conducting private personal communication with drug addicts and making efforts to seek rehabilitation homes.Islamic communication tactics used by police officers to combat drug misuse include a) recognizing the target audience of drug users, b) formulating messages, c) developing media, and d) acting as communicators. The Islamic communication method used by police officers to combat drug abuse is quite effective. It is demonstrated by the adoption of an Islamic communication approach in appealing to the community as a partner of the police in eradicating drug usage. The socialization is designed to prepare the community to report drug misuse if it occurs. This is done to keep people from being entangled in the drug trade. Islamic communication is particularly beneficial as an introspective capital in caring for family members in adult groups